2021
DOI: 10.1177/17470218211066282
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the effects of episodic future thinking on delay discounting

Abstract: Delay discounting (DD) refers to the phenomenon in which the subjective value of future rewards is reduced over time. There are individual differences in the DD rate, and increased discounting has been observed in those with various psychiatric disorders. Episodic future thinking (EFT) is the act of vividly imagining events that may happen in the future. Studies have shown that EFT could reduce DD, although inconsistent results have been reported. The aim of this meta-analysis was to clarify the efficacy with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 97 publications
1
28
1
3
Order By: Relevance
“…Thus, this might restrict the range of emotion valence, suppressing possible differences among DD between positive and negative nonalcohol EFT conditions. Even if this is the case, our result is still contradictory to two meta-analytic results suggesting negative EFT did not have effects on DD (Rösch et al, 2021; Ye et al, 2021). Nevertheless, these meta-analytic results were based on only four studies and none of them were conducted with American samples, so more study is needed to answer whether negative EFT has an effect on DD.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, this might restrict the range of emotion valence, suppressing possible differences among DD between positive and negative nonalcohol EFT conditions. Even if this is the case, our result is still contradictory to two meta-analytic results suggesting negative EFT did not have effects on DD (Rösch et al, 2021; Ye et al, 2021). Nevertheless, these meta-analytic results were based on only four studies and none of them were conducted with American samples, so more study is needed to answer whether negative EFT has an effect on DD.…”
Section: Discussioncontrasting
confidence: 99%
“…EFT refers to the capacity to imagine experiences that may occur in one's personal future (Szpunar, 2010). Recent meta-analyses show EFT could effectively reduce DD, although inconsistent results are reported (Rösch et al, 2021;Ye et al, 2021). Specifically, research has demonstrated EFT can reduce DD among individuals using substances (e.g., Bulley & Gullo, 2017;Forster et al, 2021;García-Pérez et al, 2022;Mellis et al, 2019;Patel & Amlung, 2020;Snider et al, 2016;Sofis et al, 2020;Stein et al, 2016Stein et al, , 2018.…”
Section: Episodic Future Thinkingmentioning
confidence: 99%
“…If there had been enough evidence that the rate of devaluation of future outcomes can be viewed as a mechanism of important behaviors from the perspective of general guidelines or policy, it might be valuable to affect the rate of delay discounting; therefore, a possible cause of impulsive behavior. Another promising way to affect impulsivity is through episodic future thinking (EFT) ( 56 , 57 ). It has recently been demonstrated that EFT promotes not only far-sighted decisions, but it also increases intentions to engage in preventive behaviors during the COVID-19 pandemic ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…One especially promising intervention of this kind is episodic future thinking, in which a person imagines future autobiographical events [31]. Laboratory studies have shown that episodic future thinking can decrease discounting of delayed rewards [32,33]. Although the evidence demonstrating that episodic future thinking can produce lasting change in health behavior is limited, small early studies show promising results in the domains of medication adherence [24] and smoking cessation [34].…”
Section: Discussionmentioning
confidence: 99%